MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SDN WANASUKA - Rati Supriatin; Dini Komalasari; Teti Ratnawulan; Lilis Suwandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Human resources are a key factor in improving the quality of education. The quality of teacher and educational staff management significantly determines the success of the learning process and the achievement of educational goals. However, in practice, human resource management in elementary schools, especially in rural areas, still faces various limitations. The focus of this research covers Henry Fayol's management functions: planning, organizing, implementing, coordinating, and supervising, as well as their impact on educational quality. This study aims to describe and analyze the application of human resource management in improving the quality of education at SDN Wanasuka, Pangalengan District, Bandung Regency. This study used a qualitative approach with a case study method. The research subjects included the principal, teachers, and educational staff. Data were collected through interviews, observations, and documentation studies, then analyzed using data reduction techniques, data presentation, and conclusion drawing. The results show that human resource management at SDN Wanasuka has been implemented through planning, organizing, implementing, coordinating, and supervising. Human resource planning and coordination have been running quite well, while human resource development and evaluation are still suboptimal due to limited human resources and infrastructure. The main supporting factors include principal leadership and teacher commitment, while inhibiting factors include limited human resources and teacher administrative burdens. The study's conclusions indicate that human resource management plays a strategic role in improving educational quality, but ongoing strengthening and evaluation of human resources is necessary.